Mutant Exon1 Huntingtin Aggregation is Regulated by T3 Phosphorylation‐Induced Structural Changes and Crosstalk between T3 Phosphorylation and Acetylation at K6. (23rd March 2017) - Chiki, Anass; DeGuire, Sean M.; Ruggeri, Francesco S.; Sanfelice, Domenico; Ansaloni, Annalisa; Wang, Zhe‐Ming; Cendrowska, Urszula; Burai, Ritwik; Vieweg, Sophie; Pastore, Annalisa; Dietler, Giovanni; Lashuel, Hilal A.
Abstract: Herein, we used protein semisynthesis to investigate, for the first time, the effect of lysine acetylation and phosphorylation, as well as the crosstalk between these modifications on the structure and aggregation of mutant huntingtin exon1 (Httex1). Our results demonstrate that phosphorylation at T3 stabilizes the α‐helical conformation of the N‐terminal 17 amino acids (Nt17) and significantly inhibits the aggregation of mutant Httex1. Acetylation of single lysine residues, K6, K9 or K15, had no effect on Httex1 aggregation. Interestingly, acetylation at K6, but not at K9 or K15, reversed the inhibitory effect of T3 phosphorylation. Together, our results provide novel insight into the role of Nt17 post‐translational modifications in regulating the structure and aggregation of Httex1 and suggest that its aggregation and possibly its function(s) are controlled by regulatory mechanisms involving crosstalk between different PTMs.